Spontaneous trans-anal extrusion of caudally migrated ventriculo-peritoneal shunt tip in a child: a case report - Sabyasachi Bakshi (Surgical Case Reports)
Abstract Background Bowel perforation caused by the ventriculo-peritoneal shunt is a rare occurrence with an estimated incidence rate of 0.1% to 1.0% among all cases of VP shunt displacement. This is an unusual report of spontaneous trans-anal extrusion of caudally migrated ventriculo-peritoneal shunt tip in a child. Literature was reviewed to find out therapeutic strategies. Case presentation An asymptomatic 8 months old boy presented with spontaneous trans-anal extrusion of caudally migrated left-sided Chhabra type of ventriculo-peritoneal (VP) shunt for last 1 day, following surgery for hydrocephalus initially done 3 months ago. He had no features of peritonitis or encephalitis. Digital X-ray of the whole abdomen in postero-anterior view in erect posture was only evident of the expulsion of radio-opaque distal catheter tip through the anus into the exterior. Noncontrast-enhanced computed tomography scan (NCCT) of brain showed proximal catheter in the lateral ventricle of the brain. Under sedation, the distal part of the VP shunt catheter was resected out, aseptically, over the abdomen and pulled out gently through the anus. The proximal catheter part along with the reservoir was removed through a separate incision in the neck and sent for bacteriological study, which came out later to be negative. Postoperatively, the child was put on a prophylactic antibiotic and 3 weeks later another VP shunt was placed in the contralateral side. Conclusions Spontaneous trans-anal extrusion of VP shunt tip is a surgical emergency. The whole catheter must be removed aseptically in such a way that both contamination of the cerebral cavity and spillage into the peritoneum can be avoided. Awareness of this unusual complication among surgeons is needed for early recognition, management, and timely intervention to minimize morbidity.